1997
DOI: 10.1142/s0218625x97000110
|View full text |Cite
|
Sign up to set email alerts
|

ATOMIC STRUCTURE OF THE In ON Si(111)(4 × 1) SURFACE

Abstract: The atomic structure of the In on Si (111)(4×1) surface has been determined using direct methods applied to transmission electron diffraction data. It consists of a zigzag chain of In atoms and a region of silicon including a dimer chain. The structure is sufficiently similar to recent models of the Au on Si (111)(5×2) and metal on Si (111)(3×1) structures, that some preliminary generalizations on the linear n×1 and n×2 Si(111) reconstructions can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Growth of Si(111)-4 Â 1-In on vicinal Si(111) can produce a single domain structure, with the atomic chains aligned along the step edges [13,20]. While various models have been proposed for Si(111)-4 Â 1-In [19,21], a recent surface X-ray diffraction study has produced a structure that resolves various apparent inconsistencies in previous experimental results [22]. In particular, the model has two inequivalent types of In atom, in agreement with XPS results [23].…”
Section: The Si(111)-4 â 1-in Structurementioning
confidence: 99%
“…Growth of Si(111)-4 Â 1-In on vicinal Si(111) can produce a single domain structure, with the atomic chains aligned along the step edges [13,20]. While various models have been proposed for Si(111)-4 Â 1-In [19,21], a recent surface X-ray diffraction study has produced a structure that resolves various apparent inconsistencies in previous experimental results [22]. In particular, the model has two inequivalent types of In atom, in agreement with XPS results [23].…”
Section: The Si(111)-4 â 1-in Structurementioning
confidence: 99%
“…The GA has since also been applied to several unknown structures such as In on Si(lll) 4 × 1 (Collazo-Davila, Marks, Nishii & Tanishiro, 1997), TiO2(100) 1 × 3 (Landree, Marks, Zschack & Gilmore, 1997) and Au on Si(lll) 6 × 6 (Marks, Grozea, Feidenhans'l, Nielsen & Johnson, 1997) with equally encouraging results.…”
Section: Discussionmentioning
confidence: 99%
“…This system was characterized structurally [5][6][7][8][9] and electronically [10,11]. In these works it was found that the In atoms were organized into linear chains of atoms, and that the electronic properties appeared to be highly anisotropic, with metallic behavior indicated by band crossings of E F along the chains.…”
Section: X1 Reconstruction: 1deg [4]mentioning
confidence: 99%